OPISA Booklet with QR Code Technology: Promoting Green Community Education for Sustainable Waste Management - Yulia Eka Yanti; Tety Nur Kholifah; Hendra Rustantono; Hamidi Rasyid; Paramitha Cahyani (AL-ISHLAH: Jurnal Pendidikan, 2024)
Despite the increasing environmental challenges, public awareness of proper waste management, particularly in Indonesia, remains low. This research aims to develop and evaluate the effectiveness of a QR code-based waste sorting booklet to promote practical waste management practices in households and educational institutions. The research method used is development research with the Plomp development model. A one-group pretest-posttest design is used in the study. Forty elementary school pupils from Palaan Village and Karangsari Village served as the research subjects. Initial information on the state of waste management in the neighborhood was gathered through observation and interview tools. Survey tools were employed to gauge how the community and pupils responded to the booklet's use and the degree of green community that had been established following the implementation of the waste management strategies it suggested. As a result of the research, booklets (OPISA) based on QR Code Technology were created to achieve green community education that is both legitimate and useful. These booklets have a 95% validity rating from material professionals and media experts with extremely good standards. In the meantime, the booklet has a medium level of efficacy in achieving a green community, as indicated by the moderate criteria's N-gain value of 0.44 for green community education. In the meantime, 85% of participants who responded to the booklet's use met the very good criteria, according to user response statistics. In order to raise public awareness of the significance of properly processing waste and creating a clean and healthy environment, the study's conclusion explains how the OPISA booklet can assist the community, particularly in educational institutions, in implementing practical and efficient waste management. It can also help to expand the green community in the school environment.